The wings of Poppy Pendleton [large type] - Dobson, Melanie (Center Point Large Print, 2024)
"1907. On the eve of her fifth birthday, Poppy Pendleton is tucked safely in her bed, listening to her parents entertain New York's gilded society in their Thousand Islands castle; the next morning, she is gone, and her father is found dead in his smoking room. 1992. Though Chloe Ridell lives in the shadows of Poppy's castle, now in ruins, she has little interest in the mystery that still captivates tourists and locals alike. She is focused on preserving the island she inherited from her grandparents and reviving their vintage candy shop. Until the day a girl named Emma shows up on Chloe's doorstep, with few possessions, save a tattered scrapbook that connects her to the Pendleton family. When a reporter arrives at Chloe's store, asking questions about her grandfather, Chloe decides to help him dig into a past she'd thought best left buried. The haunting truth about Poppy, they soon discover, could save Emma's life, so Chloe and Logan must work together to investigate exactly what happened long ago on Koster Isle." -- Provided by publisher.